Testament examination - Kipouràs, Pàvlos (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The testament’s examination should be methodologically approached very carefully by the document examiner. He has to take into consideration the clinical condition of the presumed testator, the particular historical circumstances of the testament’s production, and information regarding the age of the writer and his personal history. Presentation of different cases with particularities which could orientate the investigation’s hypothesis and lead to the right conclusion.
Keywords: testament; testator; oprogramowanie; fałszerstwo; scenariusz; atramenty bezpieczne; mózg